Harvesting conductive heat loss of interfacial solar evaporator for thermoelectric power generation. (25th May 2022) - Li, Haoran; Wang, Shiming; Yan, Zhe; Niu, Xiaojuan; Sun, Xinri; Hong, Wenpeng
Graphical abstract: Highlights: The conductive heat loss of an interfacial photothermal evaporator is harvested. The evaporation rate is up to 4.51 kg m -2 h −1 with excellent salt-resistance. The device obtains a considerable power density of 1.2 W m −2 at 4 suns. The output current becomes stable within 2 min if the light intensity is changed. Abstract: The solar-driven interfacial water evaporation technique enables to sustainably produce potable water from sewage, wastewater, and seawater. Limited by the advanced functional materials and structures, however, the contradiction between high evaporation rate and low heat loss needs to be further optimized in terms of improving energy efficiency. Herein, a two-dimensional solar absorber in which the vertical substrate pumps water to the top surface for sustainable evaporation and reducing heat conduction channels between the evaporation surface and the bulk water is introduced. In addition, the surplus heat of the solar absorber is directly and quickly conducted to a thermoelectric device for electricity generation. This configuration endows the hybrid device with a power density of 1.2 W m −2 at an external resistance of 4 Ω together with an evaporation rate of 4.51 kg m −2 h −1 at 4 suns illumination. Importantly, both the fast response of the hybrid device to the optical concentration and the repeatability of the output current are well supported. Such a hybrid device provides an opportunity to construct an on-site and/or off-network water treatment system with low energy consumption and trade investment.